REMOVAL OF AMOXICILLIN FROM AQUEOUS SOLUTIONS USING MODIFIED BENTONITE - Aseel M. Naji; Ziad T. Abd Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The objective of this study is to modify Iraqi natural bentonite (NB), a readily accessible and low-cost raw material, using various techniques and to explore the possible use of it as an adsorbent for the elimination of amoxicillin (AMX) from aqueous solutions through batch system studies. Chemical and physical processes were used to create the modified bentonite (MB): (1) NB was mixed with cationic surfactants (long and short alkyl chain surfactants), and (2) heat activation created calcined bentonite. The synthesized MB is characterized by surface area, "scanning electron microscopy" (SEM), and "Fourier transform infrared spectroscopy" (FTIR). There are many variables that affect how much AMX is eliminated, such as contact time, pH of solution, rate of agitation, initial concentration, and dose of the sorbent. The results showed that the Freundlich and pseudo-second-order models fit the experimental data better, with maximal removal efficiencies for calcined, long, and short alkyl chain modified natural bentonite being 94%, 70%, and 96%, respectively. The results of the trials showed that the modifications improved NB’s capacity to extract AMX from aqueous media.